Mitochondrial Genomics Reveals Shared Phylogeographic Patterns and Demographic History among Three Periodical Cicada Species Groups. (8th March 2019) - Du, Zhenyong; Hasegawa, Hiroki; Cooley, John R; Simon, Chris; Yoshimura, Jin; Cai, Wanzhi; Sota, Teiji; Li, Hu
Abstract: The mass application of whole mitogenome (MG) sequencing has great potential for resolving complex phylogeographic patterns that cannot be resolved by partial mitogenomic sequences or nuclear markers. North American periodical cicadas ( Magicicada ) are well known for their periodical mass emergence at 17- and 13-year intervals in the north and south, respectively. Magicicada comprises three species groups, each containing one 17-year species and one or two 13-year species. Within each life cycle, single-aged cohorts, called broods, of periodical cicadas emerge in different years, and most broods contain members of all three species groups. There are 12 and three extant broods of 17- and 13-year cicadas, respectively. The phylogeographic relationships among the populations and broods within the species groups have not been clearly resolved. We analyzed 125 whole MG sequences from all broods and seven species within three species groups to ascertain the divergence history of the geographic and allochronic populations and their life cycles. Our mitogenomic phylogeny analysis clearly revealed that each of the three species groups had largely similar phylogeographic subdivisions (east, middle, and west) and demographic histories (rapid population expansion after the last glacial period). The mitogenomic phylogeny also partly resolved the brood diversification process, which could be explained by hypothetical temporary life cycle shifts, and showed that none of the 13- and 17-year species within the species groups was monophyletic, possibly due to gene flow between them. Our findings clearly reveal phylogeographic structures in the three Magicicada species groups, demonstrating the advantage of whole MG sequence data in phylogeographic studies.